East Asian summer rainfall stimulated by subseasonal Indian monsoonal heating - Li, Shixue; Sato, Tomonori; Nakamura, Tetsu; Guo, Wenkai (Nature communications, 2023)
The responses of the East Asian summer monsoon (EASM) to the Indian summer monsoon (ISM) have been the subject of extensive investigation. Nevertheless, it remains uncertain whether the ISM can serve as a predictor for the EASM. Here, on the basis of both observations and a large-ensemble climate model experiment, we show that the subseasonal variability of abnormal diabatic heating over India enhances precipitation over central East China, the Korean Peninsula, and southern Japan in June. ISM heating triggers Rossby wave propagation along the subtropical jet, promoting southerly winds over East Asia. The southerly winds helps steer anomalous mid-tropospheric warm advection and lower-tropospheric moisture advection toward East Asia, providing conditions preferential for rainband formation. Cluster analysis shows that, depending on jet structures, ISM heating can serve as a trigger as well as a reinforcer of the rainband. The Indian and East Asian summer monsoons are found to be synchronized at the subseasonal timescale via a Rossby wave triggered by the Indian summer monsoon heating. The impact on East Asian precipitation varies with the subtropical jet structure.